Sustainable product development for small medium enterprise - Purba, Humiras Hardi; Hasibuan, Sawarni; Jaqin, Choesnul (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
Developing new products based on sustainable product development is not easy. It is necessary to consider various aspects such as price, quality, consumers, competitors, and others. Large-scale companies have the resource capacity to develop new products. However, for small and medium enterprises (SMEs) with limited capital and equipment, developing new products that are successful in the market response is a complicated job. This community service activity aims to educate SMEs about sustainable new product development and the basic procedures for developing a new product. It is carried out in collaboration with partners from PERMAI Penang, targeting Indonesian workers in Malaysia who may be trying to develop independent businesses. Specifically, this training will help participants 1) Identify the type of product to be developed, 2) Understand all aspects related to new product development, 3) Understand the standard stages of product development. By increasing the knowledge of independent entrepreneurship among workers in Pulau Pineng Malaysia, we hope that more SMEs will succeed in developing products or services for consumers. Empowering employees to prioritize their welfare by knowing the basics of new product development will create additional income for migrant workers who take part in this training.Contribution to Sustainable Development Goals (SDGs):SDG 9: Industrial Innovation & Responsible ProductionSDG 12: Sustainable Production & ConsumptionSDG 11: Sustainable Cities and CommunitiesSDG 17: Partnership for Sustainability